2015
DOI: 10.1130/g36799.1
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic controls on fault zone flow pathways in the Rio Grande rift, New Mexico, USA

Abstract: We assessed tectonic controls on the spatial and temporal distribution of fault zone flow pathways in the Rio Grande rift (New Mexico, USA) by using fault zone calcite cements as a geochemical record of syntectonic fluid flow. Cement d 18 O, d 13 C, and 87 Sr/ 86 Sr values indicate that older, large-displacement master and basin-margin faults were cemented by more isotopically evolved basinal brines than younger intrabasin faults. These data suggest that diagenetic fluids in basin-bounding faults equilibrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…This comparison shows no correlation between the timing of vein formation and glacial/interglacial cycles. This result is consistent with previous work showing that calcite in the Loma Blanca fault zone was controlled by upward migrating, endogenic fluids rather than shallow, meteorically derived fluids (20,29).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…This comparison shows no correlation between the timing of vein formation and glacial/interglacial cycles. This result is consistent with previous work showing that calcite in the Loma Blanca fault zone was controlled by upward migrating, endogenic fluids rather than shallow, meteorically derived fluids (20,29).…”
supporting
confidence: 83%
“…Alternatively, postseismic increases in the least compressive horizontal stress around normal faults may promote pore collapse at depth, also driving the upward migration of fluids (25,28). Although the exact mechanism responsible for fluid migration and vein formation in the Loma Blanca fault zone remains unknown, previous research has shown that fluids precipitating calcite cements in this and other basin-margin faults of the Rio Grande rift likely originated from several kilometers beneath the current exposures (29). Because postseismic fluid flow has been shown to begin as little as a few days after normal fault rupture (25), the timing of calcite precipitation is a reasonable proxy for the timing of individual earthquakes.…”
mentioning
confidence: 99%
“…To the east of the Colorado Plateau, along the Rio Grande rift, exhumed basin-bounding and intra-basin normal faults preserve a record of syntectonic changes to fault zone permeability due to groundwater flow and mineralization in poorly lithified siliciclastic sediments (Mozley and Goodwin, 1995;Heynekamp et al, 1999;Caine and Minor, 2009;Williams et al, 2015). These studies document progressive fluid flow localized along faults due to deformation and carbonate cementation that result in the compartmentalization of basin-hosted aquifers.…”
Section: Introductionmentioning
confidence: 97%
“…However, in its southwestern termination, it juxtaposes the Devonian Rueda Formation against the Stephano-Permian Erill Castell Formation. The Erill Castell Formation developed during the late to post-orogenic collapse of the Variscan belt (Lago et al, 2004;Martí, 1991Martí, , 1996Ziegler, 1988), evidencing the reactivation of the Estamariu thrust during the Alpine orogeny (Poblet, 1991;Saura, 2004). Rocks cropping out around the Estamariu thrust and the Cerc basin range from upper Ordovician to Miocene (Fig.…”
Section: Geological Settingmentioning
confidence: 98%